( القاضي الجرجاني بين الوساطة والاعتدال في نقد المتنبي ) (Journal of Humanitarian and Applied Sciences, 2023)
The subject of this research is the scholar “Al-Qadi Ali bin Abdulaziz Al-Jurjani”, who was known in the history of Arabic literature as a prominent critic, and for his renowned book “a mediation between Al-Mutannabi and his adversaries”. This book one of the most famous of its time saw Al-Jurjani take an impartial approach although highlighting his love of Al-Mutannabi and his poetry. It is one of the books that indicate the integrity and objectivity of its author’s critical judgments, as it showed Al-Mutanabbi’s advantages and shortcomings, the book also dealt with many aspects of literary criticism and the author’s views on them. this research plan is divided into a preface and three chapters: The first chapter deals with: Al-Qadi’s position between balancing and comparison. and the second: his reliance on the works of his predecessors and adopting their views, such as: Ibn Sallam al-Jamhi, Ibn Qutayba, Al-Amidi, and the third chapter: the researcher studied his rulings and findings between fairness and inequity.
Keywords: Al-Qadi Al-Jurjani; Al-Mutannabi; mediation; moderation; justice